Combination of JAK2 and HSP90 inhibitors: an effective therapeutic option in drug-resistant chronic myelogenous leukemia - Chakraborty, Sandip N. (Genes Cancer, 2016)
Recent studies suggest that JAK2 serves as a novel therapeutic target in Bcr-Abl+ chronic myelogenous leukemia (CML). We have reported the existence of an HSP90- associated high molecular weight network complex (HMWNC) that is composed of HSP90 client proteins BCR-ABL, JAK2, and STAT3 in wild type Bcr-Abl+ leukemic cells. Here we showed that the HSP90-HMWNC is present in leukemia cells from CML patients in blast stage, and in Imatinib (IM)-resistant 32Dp210 (T315I) leukemia cells. We found that the HSP90-HMWNC could be disassembled by depleting JAK2 with either Jak2-specific shRNA or treatment with JAK2 inhibitors (TG101209 or Ruxolitinib) and HSP90 inhibitor (AUY922). Combinational treatment with JAK2 and HSP90 inhibitors diminished the activation of BCR-ABL, JAK2 and its downstream targets. As a result, the IM-resistant 32Dp210 T315I cells underwent apoptosis. When administered in mice bearing 32Dp210 T315I leukemia, combinational therapy using Ruxolitinib and AUY922 prolonged the survival significantly. Thus, a combination of JAK2 and HSP90 inhibitors could be a powerful strategy for the treatment of CML, especially in IM-resistant patients.